Prioritised Predicted Region based Cache Replacement Policy for location dependent data in mobile environment. (4th December 2009) - Kumar, Ajey; Sarje, Anil K.; Misra, Manoj
Location Dependent Information Services (LDISs) provide information to mobile users depending on their current location. Data has to be transferred from the server to the mobile device, whenever required, due to mobile client's memory constraint. To improve system performance in mobile environment, frequently accessed data must be cached on the mobile client. In this paper, we propose a new cache replacement policy, the Prioritised Predicted Region based Cache Replacement Policy (PPRRP), which uses a cost function for data eviction based on the client's movement pattern. Earlier policies considered only the data distance. Simulation results show significant improvement in system performance with our policy.